RANCANG BANGUN APLIKASI KASIR USAHA MIKRO KECIL MENENGAH MENGGUNAKAN METODE BLOCK PROGRAMMING (STUDI KASUS : PELANGI STORE) - Agit Amrullah; Fata Aulia (Informasi Interaktif, 2022)
The existence of MSMEs is very influential for Indonesia's economic growth. MSMEs contribute to the national economy (GDP) as much as 61.1%. Many MSMEs still use conventional methods because of limited costs and knowledge that make MSME actors unable to utilize technology optimally. One of the problems faced by MSME actors is regarding recording transactions and managing goods. In dealing with the problems faced, the researchers tried to make a Point of Sales (POS) application by utilizing an android smartphone and developed by using block programming. The results of this study are in the form of an application to facilitate the Pelangi Store business actors in processing transactions and managing goods. The results obtained based on testing the Point of Sale application as a transaction were as expected, including being able to become software as service POS management for Pelangi Store, making it easier to manage goods and record sales history.Keywords: MSME, Point of Sales, Block Programming.